Clinical utility of circulating tumor DNA profiling in detecting targetable fusions in non-small cell lung cancer - Kim, Young-gon; Lee, Boram; Ha, Changhee; Lee, Cheonghwa; Jung, Hyun Ae; Sun, Jong-Mu; Lee, Se-Hoon; Ahn, Myung-Ju; Choi, Yoon-La; Park, Sehhoon; Kim, Jong-Won (Frontiers in Oncology, 2024)
IntroductionNumerous studies have suggested high concordance between tissue and circulating tumor DNA (ctDNA) comprehensive genomic profiling (CGP) tests but only few of them focused on fusions. In addition, atypical breakpoints occasionally detected from DNA-based fusion detection make interpretation difficult, and their clinical significance remains unclear. This study evaluated the clinical utility of ctDNA CGP for fusion detection.MethodsThe results of ctDNA CGP tests performed on patients with stage IV non-small cell lung cancer during routine clinical care were retrospectively reviewed. The concordance between ctDNA CGP and combined tissue test results was analyzed using CGP, immunohistochemistry, fluorescence in situ hybridization, and reverse transcription polymerase chain reaction. The clinical significance of fusions detected by ctDNA CGP, including those with atypical breakpoints at the DNA level, was assessed.ResultsIn total, 264 patients were tested with ctDNA CGP. Fusions were detected in 27 patients (10.2%), and the fusion drivers were RET (n=12, 4.6%), ALK (n=9, 3.4%), ROS1 (n=4, 1.5%), and FGFR2 (n=2, 0.8%). The overall prevalence of fusion in tissue CGP was comparable to that in ctDNA CGP. A total of 371 ctDNA-tissue test pairs were available, and the overall positive and negative percent agreement rates were 92.9% (13/14) and 100.0% (357/357), respectively. One ALK IHC-positive and ctDNA CGP-negative case did not respond to ALK-targeted therapy. Response to targeted therapy was assessed in 16 patients, and a partial response was achieved in all patients, including four with atypical breakpoints.ConclusionFusion detection using ctDNA CGP showed high concordance with tissue tests and accuracy in predicting therapeutic responses in patients with non-small cell lung cancer. ctDNA CGP may provide an important diagnostic tool for fusion detection.